Obesity-Related Cancer Burden Associated with Ultra-Processed Food Consumption Among US Adults. (29th May 2020) - Wang, Lu; Cudhea, Frederick; Eom, Heesun; Du, Mengxi; Michaud, Dominique; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Ultra-processed food (UPF) consumption is associated with excess calorie intake and weight gain. Weight gain and obesity contributes to the risk of 13 types of cancer. We aim to quantify obesity-related cancer burden associated with UPF consumption among US adults. Methods: We used a Comparative Risk Assessment (CRA) model to estimate the number and proportion of obesity-related cancer cases associated with UPF consumption among US adults aged 20 + years in 2015. The model incorporated data and corresponding uncertainty on UPF consumption estimated from a nationally representative sample of US adults who participated in the National Health and Nutrition Examination Survey 2013–2016, effects of UPF consumption on increasing calorie intake from a randomized controlled trial, estimated weight reduction in response to calorie reduction in consideration of reduced energy expenditure, BMI-cancer relative risk estimates from meta-analyses of prospective cohort studies, and the 2015 national cancer incidence obtained from Surveillance, Epidemiology, and End Results. Results: An estimated 15, 200 (95% uncertainty interval [UI]: 13, 900–16, 400) obesity-related cancer cases newly diagnosed in 2015 among US adults were associated with high UPF consumption, accounting for 1.0% (95% UI: 0.9%–1.1%) of all new cancer cases in 2015. The top 5 cancers with the largest number of new cancer cases associated with high UPF consumption were postmenopausal breast cancer (n = 3602, accounting for 1.9% of all postmenopausal breast cancer cases), endometrial cancer (n = 3590, 6.9%), kidney cancer (n = 2530, 4.3%), liver cancer (n = 1220, 3.9%), and colorectal cancer (n = 1190, 0.9%). The proportion of new cancer cases associated with UPF consumption was higher among women (1.4% [95% UI: 0.9%–1.1%]), middle-aged population (aged 45–54 years: 1.1% [95% UI: 1.0%–1.2%]; aged 55–64 years: 1.2% [95% UI: 1.1%–1.2%]), non-Hispanic blacks (1.1% [95% UI: 1.0%–1.1%]) and Hispanics (1.1% [95% UI: 1.0%–1.1%]) compared to other age, sex, and race/ethnicity groups. Conclusions: More than 15, 000 new cancer cases are estimated to be associated with UPF consumption among US adults in 2015, with middle-aged women and racial/ethnic minorities experiencing higher proportions of obesity-related cancer burden associated with high UPF consumption. Funding Sources: NIH/NIMHD.